Mauro Malang Santos an assembly of themes - Duldulao, Manuel D. (Manila Manila Books, 1975)
OPAC
"Published on the occasion of Malang's Fifth One-Man Show 9-28 October 1975"--Verso
Keywords: Santos, Mauro Malang, 1928-.; Painting, Modern -- Philippines